PSAK 109: TELAAH PENERAPANNYA PADA BAZNAS KABUPATEN SOLOK - ., RIZAL; ADELLA FITRI, SRI; MINAZZULAMI, HADIYATI (IAIN Batusangkar, 2017)
National Zakat Charity Agency (BAZNAS) in Solok regency is trusted as an agency for managingzakat, infak, and alms which are received from people for it will be distributed to eligible ones. In reality, the?inancial report of it is not referring to the statement of ?inancial accounting standards from the IndonesianInstitute of Accountants (IAI), PSAK No. 109 on the accounting of zakat, infak, and sedekah. Indeed, it is still inthe simple form re?lecting the numbers of zakat, , infak, and sedekah that has received and given to mustahik.This research aims to apply the statement of ?inancial accounting standards (PSAK) No. 109 at BAZNAS,Solok regency. Descriptive qualitative was used as the design of this research. Data are obtained throughinterview and documents. The ?indings showed that the system of fund accounting records of BAZNAS, Soloregency was still simple. It was only the records when the funds of zakat, infak, and sedekah were receivedand distributed. This ?inancial record is noted at the ledger and recapitulated in the form of withdrawal anddistribution of funds. Indeed, it was a report on receipt and distribution of zakat funds. Meanwhile, a reportreferring to PSAK No. 109 was on the report of ?inancial position, changes in funds, changes in school assets,cash ?low, and notes on ?inancial report have not been made by BAZNAS, Solok regency.